Le chiite imaginaire - Vincent Geisser (Revue des Mondes Musulmans et de la Méditerranée)
The recent rise of anti-Shia discourse in the Islamic field in France seems paradoxical, in a country where Shii Muslims can hardly be seen, let alone at the level of local or national Islamic institutions. In this article, I try and unravel the sociological enigma of such an “anti-Shiism without Shias.” Although it is related to the activity of traditional, hanbali-wahhabi preachers and theologians, one cannot solely look at this phenomenon as the expression of an “imported anti-Shiism” that would reflect the religious and political controversies which dominate the Islamic scenes in the Middle East. For these new forms of anti-Shiism also prove largely informed by the very stakes and cleavages of the French Islamic field. No longer simply conveyed by Salafist circles traditionally hostile to Shiism, it is now being reinvented by younger, “reformist” Muslim leaders who grew up in France and use anti-Shiism as a way of asserting their spiritual and communal authority.